Irfan and Intellectuality - Asdullah Shukrian (حکمت اسرا, 2011)
Islam’s mysticism (‘irfan) along with its profound principles is a reliable, intellectual system of thought which establishes a rational method for understanding the reality of the universe. The paper attempts to give a logical analysis of a few mystical principles to prove this assertion.